Effect of short term strength training on executive function in type 2 diabetes mellitus - Jani, Priya A.; Verma, Neha (International Journal of Research in Medical Sciences, 2025)
Background: Type 2 diabetes mellitus (T2DM) can lead to executive dysfunction. Many studies proved that Strength training can imrove the executive function in healthy individuals. Aim of the study is to evaluate the effect of short term strength training on executive function in T2DM. Methods: The 53 participants were divided into 2 groups equally by randomization. 5 drop outs from the study. Group A performed strength training and conventional exercises where as group B performed only conventional exercises. There were total 12 sessions for bothe groups. Sessions were given thrice a week for total 4 weeks. Pre and post measures of digit symbol substitution test (DSST), trail making test (TMT) A and TMT B were taken as outcome measures of executive fucntion. Results: Statistical result of 48 participants from Independent t-test showed significant difference between both groups which explains improvement in executive function after short term trength training. Conclusions: Short term strength training can enhance the executive function among patient with T2DM.